Implementasi Esp 32 Cam Dan Sensor Infrared Untuk Monitoring Pengunjung Dilokasi Wisata - Dwi Irawan; Izza Anshory (SinarFe7, 2022)
During a pandemic like this, the Covid-19 virus is easy to spread. Not only in Indonesia, but the whole world has been affected by this virus. Including almost all aspects quite affected by the presence of this Covid19 virus. Various steps have been taken by the government to reduce the spread of the COVID-19 virus. One of them is limiting the number of people in a place / room so that it can reduce the chain of spread of the covid 19 virus. The Covid-19 virus has also affected economies around the world, thus triggering an increase in theft crimes during the pandemic, making people even more restless. An appropriate security system is needed to reduce the crime of theft during the pandemic. In this case, the researcher will carry out a thesis with the title Implementation of Esp 32 cam and infrared sensors for monitoring at tourist sites. Monitoring in question is in the form of security and limiting the number of visitors. This tool uses an Esp 32 cam sensor and an infrared sensor. The application of the Esp 32 cam sensor is used as a human face detector (Face recognition) is used to detect faces based on stored facial data that can open the door, so that other people cannot open the door. Meanwhile, infrared sensors are used as a system for limiting the number of tourist visitors that are used to count visitors who pass through the entrance and exit. Researchers use infrared sensors that will detect human objects that pass through the entrance and exit. After the visitor has reached the expected number the door will be closed automatically After the visitor has reached the expected number the door will be closed automatically. Users can also monitor security and the number of visitors through Blynk Apps via mobile phones. This system is expected to minimize the occurrence of theft and prevent the chain of spread of covid 19 not only at tourist sites but also at other crowded locations